Petrographic and Diffractometric Analysis of Drill Samples from the Iron Ore Deposits of Zatua Hills, Haut Uélé Province, DRC - Mbo, Levesque Makuku; Tienge, Albert Ongendangenda (Indonesian Journal of Earth Sciences, 2024)
Seven samples were selected from various facies of geological formations intersected by the drill holes for petrographic analysis, supplemented by diffractometry. The goal was to identify the mineralogical composition of Banded Iron Formations (BIFs), the associated parageneses, and elements deleterious to the metallurgical processing of iron ore. Field tests, based on geophysical maps, were conducted to identify high-prospectivity sites characterized by low magnetic susceptibility and hematite richness, followed by sampling and drilling to confirm mineralization. Selected samples from characteristic facies in contact with iron ores underwent petrographic analysis using optical and scanning electron microscopy, supported by diffractometric analyses to ensure accurate mineralogical identification. The study revealed the presence of hematitic BIF, predominantly composed of weakly aggregated euhedral and subhedral martite grains, with evidence of some leaching. Magnetite, identified as the protore mineral, has been oxidized by fluid influence into martite (hematite), with a low presence of secondary supergene minerals. Variscite, kaolinite, and gibbsite were the main secondary minerals identified in both petrographic and diffractometric analyses, and are considered sources of phosphorus, aluminum, and silica—elements recognized as harmful in the metallurgical processing of iron and its alloys. These secondary minerals were precipitated within interstitial cavities leached between martite and hematite aggregates, forming a botryoidal texture. The BIFs of the Zatua Hills are primarily composed of hematitic iron ores associated with goethite, microplaty hematite, and secondary supergene minerals, likely formed through fluid circulation along fracture zones, shearing, and folding. Geochemical studies are recommended to complete the analysis, aiming to determine the content of these iron oxides, secondary minerals, and the degree of hydration through loss on ignition.